2003
DOI: 10.1677/joe.0.1780037
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids, eosinophils and bronchial epithelial cells: new insights into the resolution of inflammation in asthma

Abstract: Anti-inflammatory therapy in asthma is reliant on corticosteroids, particularly in their inhaled form. However, steroids are rather non-specific in their actions and they also raise concerns regarding compliance and side-effect issues. Furthermore, a small proportion of patients with asthma fail to respond to oral glucocorticoids even at high doses. This article will review the role that steroids and membrane receptor ligation play in the induction of eosinophil apoptosis together with the mechanisms by which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 51 publications
1
55
0
Order By: Relevance
“…Among the inflammatory cells participated in occurrence and development of asthma, eosinophils play a featured role [17,18] . It was considered that the inflammatory mediators and cytokines released by accumulated eosinophils in airway resulted in mucus hypersecretion, increased vascular permeability, bronchial hyperresponsiveness, smooth muscle contraction [19,20] . Furthermore, cytokines and growth factors released by inflammatory cells such as neutrophils are also involved in initiation of airway remodeling which is characterized by airway smooth muscle proliferation [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Among the inflammatory cells participated in occurrence and development of asthma, eosinophils play a featured role [17,18] . It was considered that the inflammatory mediators and cytokines released by accumulated eosinophils in airway resulted in mucus hypersecretion, increased vascular permeability, bronchial hyperresponsiveness, smooth muscle contraction [19,20] . Furthermore, cytokines and growth factors released by inflammatory cells such as neutrophils are also involved in initiation of airway remodeling which is characterized by airway smooth muscle proliferation [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils are also notoriously difficult to study for a number of reasons: their paucity in the peripheral blood of normal, healthy volunteer blood donors, the laborious isolation techniques required to ensure a pure population and their relative intractability to standard molecular biological techniques such as siRNA. Corticosteroids are known to induce significant eosinophil apoptosis, in vitro, but it is still debatable as to whether this effect is relevant in vivo [6,31,[36][37][38][39][40]. Steroid drugs are extremely effective in the majority of asthmatic patients but some, at the more severe end of the spectrum, are resistant and others experience intolerable and unacceptable side-effects [41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils and their products have been demonstrated within airways, in lung parenchyma, at the site of eczematous skin lesions and in nasal mucosa. Evidence of their armamentarium has also been detected at sites of allergic inflammation and it has been shown that they contribute to airway epithelial damage and remodelling in asthma [1,[4][5][6][7]. Therapeutic strategies that decrease eosinophil recruitment and activation or enhance resolution of inflammation by driving eosinophil apoptosis and clearance should ameliorate allergic inflammatory disease [1,3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoid treatment greatly increases the phagocytic activity of monocytes and macrophages [72,73]. Enhanced clearance of apoptotic eosinophils has been suggested to be a mechanism by which glucocorticoids help to bring about a resolution of airway inflammation in asthma [72,74]. Phagocytosis of invading neutrophils by tissue-resident macrophages is a major mechanism for resolution of inflammation [75].…”
Section: Microglial Activation In Diabetic Retinopathymentioning
confidence: 99%